Partisipasi Masjid Dalam Mendorong Tata Kelola Sampah Pedesaan Di Desa Genteng Kulon Kecamatan Genteng Kabupaten Banyuwangi - Ahmad Izza Muttaqin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2018)
The discourse about Ahlu al-Sunnah wa al-Jamaah is still very interesting among academics. This term becomes an idol for every stream and is raised within the scope affirming its status as a surviving stream of the world and the hereafter (firqah al-Najiah). Ahlu al-Sunnah wa al-Jamaah became fertile because it is supported by the hadith of the Prophet who indeed came from 73 groups of Islam only one who survived the Ahlu al-Sunnah wa al-Jamaah group. Ahlu al-Sunnah wa al-Jamaah by Said Aqil as People who have a method of religious thinking that covers all aspects of life based on the foundations of moderation, maintaining balance and tolerance. Ahlu al-Sunnah wa al-Jamaah is a school that will become a Manhaj al-Fikr, as it is only an attempt to find a middle ground between the various streams. Ahlu al-Sunnah wa al-Jamaah there is no limitations and provisions that should be the same as Imam Abu Hasan al-Asy'ari or al-Maturidi but the pillars of Ahlu al-Sunnah wa al-Jamaah understand this must-have differences and opinions in interpreting the source of religion not become the gulf as long as still holding pillars (rukn) Ahlu al-Sunnah wa al-Jamaah namely the divinity (uluhiyah), apostles (Nubuwah) and the end (al-Ma'd).